Home of the happy: a murder on the Cajun prairie - LaHaye Fontenot, Jordan (Mariner Books, 2025)
"On January 16, 1983, Aubrey LaHaye's body was found floating in the Bayou Nezpique. His kidnapping ten days before sparked "the biggest manhunt in the history of Evangeline Parish." But his descendants would hear the story as lore, in whispers of the dreadful day the FBI landed a helicopter in the family's rice field and set out on horseback to search for the seventy-year-old banker. Decades later, Aubrey's great-granddaughter Jordan LaHaye Fontenot asked her father, the parish urologist, to tell the full story. He revealed that to this day, every few months, one of his patients will bring up his grandfather's murder, and the man accused of killing him, John Brady Balfa, who remains at Angola Prison serving a life sentence. They'll say, in so many words: "Dr. Marcel, I really don't think that Balfa boy killed your granddaddy." For readers of Maggie Nelson's THE RED PARTS and Emma Copley Eisenberg's THE THIRD RAINBOW GIRL, HOME OF THE HAPPY unravels the layers of suffering borne of this brutal crime-and investigates the mysteries that linger beneath generations of silence. Is it possible that an innocent man languishes in prison, still, wrongly convicted of murdering the author's great-grandfather?"-- Provided by publisher